1983
DOI: 10.1126/science.6301009
|View full text |Cite
|
Sign up to set email alerts
|

The Radicals in Cigarette Tar: Their Nature and Suggested Physiological Implications

Abstract: The paramagnetism of cigarette tar is found to be associated with at least four different types of species. One of the types is responsible for over 80 percent of the total paramagnetism and has a signal intensity that is independent of temperature from 60 to 250 K. This non-Curie-Weiss temperature dependence indicates that the principal paramagnetic species in tar is not an organic monoradical (doublet) species but instead is a donor-acceptor excimer with a paramagnetic excited state and a diamagnetic ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
175
0
4

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(191 citation statements)
references
References 14 publications
12
175
0
4
Order By: Relevance
“…Cigarette smoking, with its .4000 compounds and 10 14 free radicals per puff, represents a major environmental stress (26)(27)(28)(29). Consistent with our observations in the SAE, several studies have demonstrated that cigarette smoke in vivo and in vitro can mediate differences in the methylation status of individual genes in lung cells as well as non-lung cells.…”
Section: Smoking-associated Changes In Lung Dna Methylationsupporting
confidence: 76%
See 1 more Smart Citation
“…Cigarette smoking, with its .4000 compounds and 10 14 free radicals per puff, represents a major environmental stress (26)(27)(28)(29). Consistent with our observations in the SAE, several studies have demonstrated that cigarette smoke in vivo and in vitro can mediate differences in the methylation status of individual genes in lung cells as well as non-lung cells.…”
Section: Smoking-associated Changes In Lung Dna Methylationsupporting
confidence: 76%
“…With this background, we hypothesized that cigarette smoke, with its .4000 compounds and 10 14 oxidants per puff, may have profound effects on the methylome of the small airway epithelium (SAE), the cell population that takes the initial stress of cigarette smoke and is the first site of lung pathology in cigarette smokers (26)(27)(28)(29)(30)(31)(32). In humans, the SAE consists of four major cell types: ciliated, secretory, columnar and basal cells (30,33).…”
Section: Introductionmentioning
confidence: 99%
“…7 It is postulated that smoking affects the pathogenesis of AMD by a variety of methods including promoting oxidative damage, inducing angiogenesis, impairing the choroidal circulation, and by activating the immune system including complement pathway. [8][9][10][11][12][13] Stopping smoking reduces the risk of AMD and after 20 years of cessation the risk of developing AMD is the same as for non-smokers. 14 In the last few years, the genetic factors significantly contributing to AMD risk have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The protective action of P-carotene may be explained by its anti-oxidant capacity to quench highly reactive singlet oxygen and free radical species (Krinsky, 1989). Free radicals are abundant in cigarette smoke and tar (Pryor et al, 1983) and are believed to initiate cancer by damaging DNA (Pryor, 1987). In addition, P-carotene has been hypothesised to be effective after conversion to retinol at a tissue or cellular level (de Vet, 1989).…”
Section: Discussionmentioning
confidence: 99%